Depression and increased risk of Alzheimer's dementia: Longitudinal analyses of modifiable risk and sex‐related factors: Developing topics. (7th December 2020) - Kim, Doyoung; Wang, Ruoding; Kiss, Alex; Bronskill, Susan E; Lanctot, Krista L; Herrmann, Nathan; Gallagher, Damien
Abstract: Background: Older adults with depression are at increased risk of Alzheimer's dementia (AD). Most adults with AD are women. Women have two‐fold lifetime risk of depression. It is not known how sex influences the risk of depression upon AD. Method: We used the longitudinal case series dataset from National Alzheimer's Coordinating Center for analysis. Older adults (age 50+) with normal cognition, who visited memory clinics across the United States from September/2005 to December/2019, were followed from initial visit until first diagnosis of AD or loss to follow up. Multivariable survival analyses were conducted to determine if 1) recent and remote depression were independently predictive of AD, 2) this risk differed between the sexes, and 3) sex modifies this risk. Result: 652 of 10, 739 enrolled subjects developed AD over a median follow‐up of 55.3 months. Only recently active depression (within the last 2 years) was associated with increased risk of AD (HR=2.0; 95%CI, 1.5‐2.6) independently of other significant risk factors. After stratification by sex, recent depression was an independent predictor of AD in females (HR=2.3; 95%CI, 1.7‐3.1) but not in males (HR= 1.2; 95%CI, 0.7‐2.1). No interaction between recent depression and sex in predicting the risk of AD was observed (HR=1.5; 95%CI, 0.8‐2.8). Conclusion: Only recent history of depression was associated with higher risk of AD. This risk was significant only in women. Future analyses should determine if current findings extend to other populations and may be explained by variable distribution of neurobiological or other modifiable risk factors between the sexes.